Rusofonija, runet in ruski jezik - Hye-Hyun, Nam (Slavistična revija, 2012)
For the purpose of promoting the Russian language, whose sphere of functioning is gradually diminishing in the world, specifically in the Post-Soviet era, the ideas of "Rusophonia" and "Russian World" were suggested in Russia. Both of these ideas are an effort to create a supra-governmental and supra-national network structure that unites all Russian speakers and those who are interested in the Russian culture, regardless of their nationalities. And to create such a network structure, recently Russia turned to the possibilities of the Internet. In this article we analyze current situation with the Russian language in relation to the expanding limits of Runet (Russian-language Internet) in the Post-Soviet nations and also on the perspectives of the future of the Russian language on Runet.
Keywords: elektronski mediji; internet; Runet; Rusifonija; Ruski svet; Russian; ruščina; spletni portali